The influence of standardization and automation towards risk management effectiveness in finance shared service centre - Fazli, Sibon (2020)
The objective of this study is to examine the influence of standardization and automation towards risk management effectiveness in finance shared service center. There are two independent variables are being investigated to see the relationship towards risk management effectiveness which are standardization and automation process in finance shared service center. This study is determining the relationship between independent variables and the dependent variable by distribution questionnaire to the focus group which are the executives and managers in the company. Furthermore, those finding has been analyze using SPSS by using descriptive, correlation and multiple regression analysis. The findings showed that there were moderate levels of standardization process, process automation and risk management effectiveness as perceived by the managers and executives of Finance shared service centers. Meanwhile, there were positive and strong correlations between standardization process and process automation toward the risk management effectiveness. It also concluded both standardization process and process automation were significant predictors and contributors to the variances of risk management effectiveness. For future study, it is recommended that new research can be done using other research method such as qualitative and mixing between quantitative and qualitative for a strong result. Instead, it is recommended that next research can use larger sampling size and adding more attributes for risk management effectiveness.